1984
DOI: 10.1111/j.1365-2125.1984.tb02427.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable oral availability of sustained release propranolol when co‐ administered with hydralazine or food: evidence implicating substrate delivery rate as a determinant of presystemic drug interactions.

Abstract: I A study was made of the influence of hydralazine on the oral availability of a sustained release formulation of propranolol (Inderal LA®). Sustained release propranolol 160 mg was given orally either alone or in combination with oral hydralazine 25 mg on separate occasions to six healthy volunteers. Blood and urine samples were collected post-dosing over 34 h. 2 Peak concentrations of propranolol, time to peak and area under the plasma concentration-time curve (AUC) were not altered by co-administration of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…AUC of propranolol ng. h-ml ~ in the 7 subjects who participated both in the current and the previous study [ That the phenomenon was transient is also apparent from the fact that food did not enhance the bioavailability of propranolol given in a slow-release formulation [4,9]. A recent study on a propranolol-like compound, propafenone, showed that the extent of the food effect might depend upon the extent of oral clearance [15].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…AUC of propranolol ng. h-ml ~ in the 7 subjects who participated both in the current and the previous study [ That the phenomenon was transient is also apparent from the fact that food did not enhance the bioavailability of propranolol given in a slow-release formulation [4,9]. A recent study on a propranolol-like compound, propafenone, showed that the extent of the food effect might depend upon the extent of oral clearance [15].…”
Section: Discussionmentioning
confidence: 72%
“…Rather, the increased bioavailability appeared to be secondary to a transient reduction in the hepatic extraction of propranolol. Such a reduction might be consequent to a transient increase in the hepatic delivery rate of the drug [5,8,9]. If the increase were sufficiently short-lived it could also help to explain why the increased availability of propranolol was not associated with a corresponding reduction in the total availability of any (oxidative) metabolite, but only with a delay (reduced AUC(0-60 min) in the appearance of one (NLA) or more of these metabolites.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Walle and co-workers suggested that the food-induced increase in propranolol bioavailability is proportional to the amount of protein in the meal (Walle et aI., 1981), but Mclean and coworkers reported similar increments after a predominantly carbohydrate stimulus and a high protein-lipid meal (Mclean et aI., 1981). Recent observations indicate that food does not reduce the presystemic clearance of propranolol when the drug is given in a slow-release formulation (Byrne et at, 1983). This is analogous to findings with hydralazine (Liedholm et aI., 1983) and is of considerable mechanistic interest (see section 5).…”
Section: P-adrenoceptor Antagonistsmentioning
confidence: 70%
“…Specifically, it has been demonstrated that a transient increase in splanchnic-hepatic blood flow -as modelled on recorded food-drug interactions (Melander et al, 1977b) -could enhance the oral bioavailability of such drugs even if a flow-independent model of the liver itself were assumed (Mclean et al, 1978). In support of this model, 292 ingestion of the vasodilator hydralazine, which is known to enhance splanchnic-hepatic blood flow, has been found to increase the bioavailability of co-administered propranolol (Mclean et al, 1980), and administration of a slow-release formulation of propranolol ablated both the interaction associated with hydralazine and with food (Byrne et al, 1983). Furthermore, co-administration of the vasodilator glyceryl trinitrate and the high clearance drug dihydroergotamine gave a similar increase in dihydroergotamine bioavailability .…”
Section: Phasic Flowmentioning
confidence: 83%